Stressors and coping strategies among people affected by Ebola Virus Disease (EVD) in West Africa: A qualitative study across multiple levels of the social ecology - Thomas M. Crea; Elizabeth K. Klein; Oladoyin Okunoren; K. Megan Collier; Charles Currie; Montray Smith; Stephen Sevalie; Bailah Molleh; Yusuf Kabba; Abdulai Kargbo; Joseph Bangura; Henry Gbettu; et al. (Heliyon)
The 2014-16 Ebola Virus Disease (EVD) epidemic in West Africa is the most fatal on record and resulted in significant psychosocial and economic implications for those affected. Coping strategies and social supports can abate the effects of traumatic experiences on emotional wellbeing, and existing studies highlight a variety of strategies used by EVD survivors in the aftermath of outbreaks. The purpose of this qualitative study is to examine EVD-related stressors and sources of support among those affected by the EVD outbreak in Sierra Leone across multiple levels of the social ecology. Purposive maximum variation sampling was used to recruit n = 228 participants for key informant interviews (n = 42) in five districts and focus group discussions (n = 27) in three districts. Data analysis was guided by grounded theory and thematic content analysis approach, with teams of coders using open and axial coding on all transcripts. Results showed that most stressors (isolation, rejection, associative stigma, and discrimination) and sources of support (tangible and intangible kindnesses) emerged at the community level. The most frequent family-level stressor was lack of financial resources, while at the individual level, destruction of property and fear of disclosing EVD infection were the most stressful. Spirituality and religion emerged as significant coping strategies among participants, specifically dependence on God and expressing gratitude. Participants also mentioned avoiding talking about Ebola and forgetting about the past as coping strategies, which raises questions about posttraumatic stress and highlights the importance of further research. This study's findings highlight that even in the absence of formal government support, survivors of the EVD outbreak showed significant resilience in managing and rebounding from the crisis – and highlight the systemic inequalities that forced communities to develop such localized coping strategies.